Goat meat production & quality - Kadim, I. T. [ (Isam T.)]; Mahgoub, O. [ (Osman)]; Webb, E. C. [ (Edward Cottington)] (CABI, 2012)
Covers important areas of goat meat production. This title discusses the role of genetics, breeding, reproduction, and nutrition in producing good quality, profitable goat meat. It addresses the mineral, amino acid and fatty acid composition of goat meat, highlighting its health benefits over other red meats